ANALISIS PENGARUH VALUE CHAIN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KEPUASAN PELANGGAN PADA PT POS INDONESIA DI GRESIK - Jajuk Suprijati (Kompetensi (Competence : Journal of Management Studies), 2016)
Increasingly tight competitive world of business today . Corporate leaders and staff have to work extra hard to win the competition and still exist in the business world . PT Pos Indonesia also in a position like other businesses , competitors PT Pos Indonesia engaged in freight forwarding services more and more like TIKI , JNE , LTH and so forth . All these companies are competing to provide satisfaction to its customers by providing the best service possible , so that it becomes a fanatical customer and not move to other delivery services company . In particular, it should also be done by PT Pos Indonesia branch Gresik which is the object of study This study examines how to implement CRM Value Chain ( custumer Relationship Management ) on PT Pos Indonesia branch of Gresik that there is a bond between manufacturers and customers as well as its influence on customer satisfaction . This study measured the effect of independent variables are used , the customer portfolio ( X1 ) , customer intimacy ( X2 ) , Network Development ( X3 ) , proportion of value ( X4 ) and Customer Life Cycle ( X5 ) Customer satisfaction is the dependent variable ( Y ) .Results from this study is that all the independent variables and the dependent is a valid and reliable as well as data distribution is normal . To avoid the classical assumption of multicollinearity in the independent variables and avoid heteroscedasticity between independent variables and residual . In the F test showed that the resulting model is suitable to determine the effect of independent variables on the dependent variable . At t test showed that the customer portfolio variables ( X1 ) and Customer Intimacy ( X2 ) partially no significant effect on customer satisfaction while variable network development ( X3 ) , proportion of value ( X4 ) and Customer Life Cycle ( X5 ) partial effect on satisfaction customers .